(untitled) (International Journal of Innovative Technologies in Economy, 2018)
Article is devoted to the assessment and analysis of the level of financial security of the economies of the countries of Central Asia, and the definition of the criteria for the development of the financial system, its support and approval in the current economic situation. The urgency of the article is due to the fact that in the current situation the problem of ensuring financial security becomes systemic, it affects and connects individual countries, regions, economic entities, politics, economy, finance, etc. Integration of countries with a guarantee of financial security will contribute to the sustainable development of the region’s economy to financial risks.